Industri Televisi Swasta Indonesia dalam Perspektif Ekonomi Politik - Budi HH, Setio (Jurnal ILMU KOMUNIKASI, 2004)
The presence of commercials television in Indonesia had many dynamics. Some background shown the development of commercial television, first it was rise from the government problems facing with spillover of transnational broadcasting via parabola antenna, second, the pressured of the international institutions relating with regulationsÃ¢â‚¬â€liberalization (against the state monopoly of mediaÃ¢â‚¬â€œTVRI), third, the pressured of national business entities (after the restriction of advertising in television, 1980). This article questions therefore what is the implications of commercial televisions in Indonesia, especially to the public that seems didnÃ¢â‚¬â„¢t have voice enough for the presence of the those commercial elevisions.